PENGGUNAAN TEKNOLOGI INFORMASI DAN SISTEM AKUNTANSI MANAJEMEN SEBAGAI PEMODERASI DALAM HUBUNGAN ANTARA INTENSITAS PERSAINGAN PASAR TERHADAP KINERJA PERUSAHAAN - Isma Coryanata (Program Magister Akuntansi Unsyiah, 2011)
The main objective of this study is to examine increasing in the market competition about the application of manufacturing technology, deregulation of economies and privatization of government owned enterprises makes decision makers to be management accounting system (SAM) information more important. This research reports the results of a study which offers an explaination for the relationship between intensity of market competition and business unit performance by incorporating into the model the use of managent accounting systems information by managers as moderating variable. To asses the relationship, data were colleced from 87 enterprises in service. The result of this research indicate that the intensity of market competition is a determinant of the use of the information MAS which, in turn, is a determinant plays a mediating role in the relationship between the intensity of market competition and business unit performance. An interpretation of the result is that those organizatations which use the information can effectively face competition in the market and thereby improve performance.Key words: technology be management accounting system informatiointensity of market competition and business unit performance